Rumen microbiota regulates IMF deposition in Xizang sheep by activating the PPARγ transcription factor: a rumen-muscle axis perspective - Cheng Pan; Junru Pan; Yangzong Zhaxi; Haiyan Li; Zhenzhen Zhang; Feng Guan; Jiacuo Jinmei; Zhaxi Baijiu; Sangzhu Baima; Quzhu Yixi; Tianzeng Song; Wangsheng Zhao (mSystems)
ABSTRACT The interaction between microbiota and muscle by the rumen-muscle axis and its impact on sheep meat flavor has received little attention. This study selected Xizang sheep under summer and autumn grazing conditions as models for different rumen bacteria and intramuscular fat (IMF) to attempt to address the current research gap. Specifically, the deposition characteristics of IMF and the expression of lipid metabolism genes in Xizang sheep were determined; 16S rDNA sequencing technology and gas chromatography were used to study the rumen microbiota and its metabolic products, short-chain fatty acids (SCFAs); RNA sequencing was used to identify the transcriptome of the rumen epithelium. Based on the above results, we proposed the hypothesis that the flavor of Xizang sheep meat is regulated by the microbiota-rumen-muscle axis. SCFAs produced in the rumen of Xizang sheep are absorbed by the rumen epithelium under the regulation of the solute carrier family genes (SLC). SCFAs can directly reach muscle tissue through the circulatory system and then activate the expression of the peroxisome proliferator-activated receptor Gamma (PPARγ) gene through the rumen-muscle axis. The expression of fat synthesis genes carnitine palmitoyltransferase II (CPT2), fatty acid synthase (FAS), patatin-like phospholipase domain-containing 2 (PNPLA2), and stearoyl-CoA desaturase 1 (SCD1) is correspondingly upregulated, promoting the deposition of IMF in Xizang sheep and thus affecting its flavor. This study introduces the theory of the microbiota-rumen-muscle axis into the research of the flavor of ruminant animal food, comprehensively elucidating the regulatory mechanism of the flavor of Xizang sheep meat.IMPORTANCEOur study employed a multi-omics approach to reveal how the rumen microbiota regulate muscle lipid metabolism in Xizang sheep through the activation of the PPARγ transcription factor. Importantly, by developing models of Xizang sheep with varying rumen microbial communities and muscle fatty acid profiles, we established the critical role of the microbiota-rumen-muscle axis in determining the flavor of Xizang sheep meat. This finding suggests that modulating the composition of the microbial community could serve as a strategy to improve the flavor of ruminant-derived food products. These insights provide valuable understanding of the complex interactions between rumen bacteria and mutton flavor, offering new approaches for research in this field.